Respuestas

2012-08-22T23:28:04+02:00

5x+6=11---------------------------------->x=1

x+3x+6=10------------------------------->x=1

8x+8x=32--------------------------------->x=2

5(2x)=100--------------------------------->x=10

4x/2=10------------------------------------>x=5

2012-08-22T23:43:18+02:00

3x -1   = 2x + 5 
          3(6)-1  = 2(6) + 5    

          18 - 1  = 12 + 5        
                17 = 17


 3x + 1    = 2x + 3 
          3(3) + 1 = 2(3) + 3 
          9 + 1     = 6 + 3 
                  10 = 9


   

x - 6 = 2

                         x + -6 = 2 
                  x  + -6 + 6 = 2 + 6 
                          x + 0 = 8 
                                x = 



2x+6 = 20

                  2x + 6    = 20 
                         2x   = 20 - 6           
                           2x = 14                 


                          2x 14 
                           2      2

                             x = 7




 4x - 9 = 2x + 3 
              4x + - 9 = 2x + 3          
                4x - 2x = 3 + 9             
                     2x 12                
                      2      2

                        x = 6